ANALISIS PENGARUH LITERASI KEUANGAN, SIKAP KEUANGAN DAN KEPRIBADIAN TERHADAP PERILAKU PENGELOLAAN UMKM DI KABUPATEN ENDE - Laurentius Dominicus Gadi Djou (Magister Manajemen STIE Bank BPD Jateng, 2019)
This research have purposes to determine (1) the effect of financial literacy on financial managementbehavior, (2) the effect of financial attitudes on financial management behavior, (3) the influence of personality onfinancial management behavior on large and retail trade MSMEs; car and motorcycle repair in EndeRegency.This research is included in associative causal research. The subjects of this study were all owners ofMSMEs in wholesale and retail trade; car and motorcycle repairs in Ende Regency as many as 96 MSMEs. Datacollection techniques using a questionnaire. Validity and reliability tests were carried out on 96 people outside thesubject who were registered as large and retail trade MSMEs; car and motorcycle repair in Ende Regency.Analysis prerequisite tests include linearity test, multicollinearity test, and heteroscedasticity test. Data analysistechniques with multiple linear regression. The results showed that (1) financial literacy variables had a positiveand significant effect on financial management behavior variables of 0.390. (2) financial attitude variables have apositive and significant influence on financial management behavior of 0.434. (3) personality variables have apositive and significant influence on financial management behavior of 0.120.